Correlation of Total Polyphenolic Content with Antioxidant Activity of Hydromethanolic Extract and Their Fractions of the Salvia officinalis Leaves from Different Regions of Morocco - Zakaria Khiya; Yassine Oualcadi; Abderrahmane Gamar; Fatima Berrekhis; Touria Zair; Fatima EL Hilali (Journal of Chemistry)
The purpose of this study is to determine the total content of phenols, flavonoids, and condensed tannins, as well as on the antioxidant activity of the extract, and their fractions were measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), phosphomolybdate reduction (or total antioxidant capacity), and cyclic voltammetry (CV). The hydromethanolic extract of Salvia officinalis showed the highest values of total phenolic (176 mgGAE/g of extract) and condensed tannins (162.53 mgEC/g of extract) from the Boulemane and Khenifra regions, respectively. The results showed that the best DPPH assay was found in the ethyl acetate fraction of Salvia officinalis leaves of the Boulemane region (IC50 = 0.002 mg/ml). For the ethyl acetate and butanolic fractions of Salvia officinalis leaves, those collected from different regions have a better reducing capacity (EC50 = 0.021 mg/ml, respectively). For the total antioxidant capacity, the best activity was found in the aqueous fraction of Salvia officinalis leaves of the Boulemane region (108 mgGAE/g of extract). By the cyclic voltammetry method, hydromethanolic extract of Salvia officinalis leaves from the Boulemane region showed an important result (288.8 mgGAE/g). There was a positive correlation between total phenol content (TPC), condensed tannin content (TCT), and total antioxidant capacity (TAC) (r = 0.932, r = 0.896, respectively). The main compounds that have been identified in the hydromethanolic extract of Salvia officinalis are ascorbic acid, gallic acid, 4-hydroxybenzoic acid, tannic acid, and rutin. Due to their antioxidant property, the leaf extracts from Salvia officinalis are used as natural preservative ingredients in food and/or pharmaceutical industries.